Effect of drinking, smoking, and smartphone overdependence on drug addiction among Korean adolescents - Jeong, Jaehee; Lee, Wanhyung; Lee, Seunghyun (Frontiers in Public Health, 2025)
IntroductionAdolescent brain development increases vulnerability to drug addiction due to diminished impulse control and the presence of mental health disorders. Alcohol consumption, smoking, and smartphone overdependence have been individually associated with higher drug use, but their combined impact on adolescent drug addiction remains underexplored. This study examines the interaction effects of alcohol consumption, smoking, and smartphone overdependence on drug addiction risk among adolescents.MethodsData were obtained from the 16th Korea Youth Risk Behavior Web-based Survey (2020), including 54,948 students from 793 schools. Interaction effects of alcohol consumption, smoking, and smartphone overdependence on drug addiction risk were analyzed, along with a dose-response relationship analysis.ResultsAlcohol consumption, smoking, and smartphone overdependence were significantly associated with increased drug addiction risk. Earlier initiation of drinking and smoking was linked to a higher risk of drug addiction. A significant interaction effect between alcohol consumption and smartphone overdependence on drug addiction was observed.ConclusionsAlcohol consumption, smoking, and smartphone overdependence significantly elevate the risk of drug addiction among adolescents, with interaction effects exacerbating this vulnerability. Early initiation of drinking and smoking is particularly associated with a heightened addiction risk. A comprehensive understanding of these interaction effects and dose-response relationships is imperative for the formulation of evidence-based, targeted prevention strategies to mitigate adolescent substance use and addiction.